Pengaruh Beban Kerja, Kepuasan Kerja, dan loyalitas Kerja Terhadap Kualitas Kerja Karyawan - Indra Nara Persada; Mulawarman (Komunitas Dosen Indonesia, 2023)
This study aims to determine and analyze the effect of workload (X1), job satisfaction (X2), and job loyalty (X3) on employee work quality (Y) at PT Indomarco Prismatama Nagoya Batam Branch, either partially or simultaneously. This study uses quantitative methods, the population in this study as many as 251 employees. Then the sample was taken using the slovin formula so that a total of 72 employees were obtained. The analysis technique used is instrument test, classical assumption test, multiple regression analysis, determination test (R Square), t test and f test. As a statistical research method using SPSS. The results of the study explain that simultaneously workload (X1), job satisfaction (X2), and work loyalty (X3) have a significant influence on the quality of employee work (Y) at PT Indomarco Prismatama Branch Nagoya Batam. From the results of the T-test the variables workload, job satisfaction, and work loyalty simultaneously have a significant effect on the quality of employee work. Using the F test, the variables of workload, job satisfaction, and job loyalty have a significant influence on the quality of employee work. While the adjusted R Square value of 0.595 explains that the simultaneous variables of workload, job satisfaction, and job loyalty have a significant influence on the quality of work of employees at PT Indomarco Prismatama Branch Nagoya Batam by 59.5% while the rest is influenced by other variables not examined in this study. this research.